SENSOR ELETROQUÍMICO BASEADO EM ÓXIDO DE GRAFENO REDUZIDO E ESTANATO DE ZINCO PARA DETERMINAÇÃO DE PROMETAZINA - Andreza L. Moreira; Janevane S. de Castro; Anderson V. Chaves; Pierre B. A. Fechine; Pedro de Lima-Neto; Francisco W. P. Ribeiro; Paulo N. S. Casciano; Adriana N. Correia (Química Nova)
An innovative sensor, based on a glassy carbon electrode modified with a reduced graphene oxide and zinc stannate composite (Zn2SnO4-rGO/GCE), was developed to detect and quantify promethazine hydrochloride (PMZ) in pharmaceutical formulations, using square wave voltammetry (SWV). The morphology of the sensor was analyzed by scanning electron microscopy (SEM), which revealed the aggregation of rGO and Zn2SnO4 species. The chemical interaction between the components was investigated by electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV), showing lower charge transfer resistance and higher analytical signal in the PMZ oxidation process. The optimized analysis conditions (McIlvaine buffer pH 5.0, frequency of 80 s-1, amplitude of 25 mV and increment of 2 mV) resulted in a linear analytical curve in the range of 1.48 × 10-7 to 6.48 × 10-6 mol L-1, with low detection (1.24 × 10-8 mol L-1) and quantification (3.76 × 10-8 mol L-1) limits. The sensor demonstrated high repeatability (%RSD, relative standard deviation = 1.54) and reproducibility (%RSD = 1.89) and was effective in the analysis of PMZ in pharmaceutical samples, presenting a recovery rate of 96.62%, proving its applicability in pharmaceutical analysis.